Animal spirits how human psychology drives the economy, and why it matters for global capitalism - Akerlof, George A. 1940-; Shiller, Robert J. (Princeton, New Jersey Princeton University Press, 2010)
The global financial crisis has made it painfully clear that powerful psychological forces are imperiling the wealth of nations today. From blind faith in ever rising housing prices to plummeting confidence in capital markets, "animal spirits" are driving financial events worldwide. In this book, the authors, both economists, challenge the economic wisdom that got us into this mess, and put forward a bold new vision that will transform economics and restore prosperity. They reassert the necessity of an active government role in economic policymaking by recovering the idea of "animal spirits", a term John Maynard Keynes used to describe the gloom and despondence that led to the Great Depression and the changing psychology that accompanied recovery. Like Keynes, they know that managing these animal spirits requires the steady hand of government; simply allowing markets to work won't do it. In rebuilding the case for a more robust, behaviorally informed Keynesianism, they detail the most pervasive effects of animal spirits (i.e. human psychology), in contemporary economic life, such as confidence, fear, bad faith, corruption, a concern for fairness, and the stories we tell ourselves about our economic fortune, and show how Reaganomics, Thatcherism, and the rational expectations revolution failed to account for them. The authors then offer a road map for reversing the financial misfortunes besetting us today; they teach how leaders can channel animal spirits, the powerful forces of human psychology that are afoot in the world economy today, and making them work for and not against us.
This text provides a picture of how a capitalist economy works, especially at the macro level. It considers eight questions about the working of the economy. This provides the background that is necessary to take on other questions about macroeconomic policy, finance, bankruptcy law, and others, and to begin to answer them.
Animal Spirits. Confidence and its multipliers -- Fairness -- Corruption and bad faith -- Money illusion -- Stories -- Eight Questions and Their Answers. Why do economies fall into depression? -- Why do central bankers have power over the economy (insofar as they do)? -- Why are there people who cannot find a job? -- Why is there a trade-off between inflation and unemployment in the long run? -- Why is saving for the future so arbitrary? -- Why are financial prices and corporate investments so volatile? -- Why do real estate markets go through cycles? -- Why is there special poverty among minorities?.
Includes bibliographical references (pages 199-218) and index.
Keywords: Economics -- Psychological aspects; Finance -- Psychological aspects; Capitalism; Globalization